GENDER DISCRIMINATION IN INDONESIAN ONLINE NEWS TEXTS - Devi Mutia; Agus Hamdani (Indonesian language and literature education program Majapahit Islamic University, 2023)
Critical Discourse Analysis (CDA) can serve as a tool and method to examine the relationship between discourse, society, and culture (Fowler, 1997). Therefore, it can be said that CDA uses language to analyze inequalities in various fields such as economics, politics, social issues, culture, and education. According to Theo Van Leuween, the marginalization of certain social groups can be observed based on their presence or absence in a discourse. Some are excluded from the conversation (exclusion), while others are included in the conversation (inclusion) (Eriyanto, 2009). This research employs a descriptive qualitative method with the note-taking technique. The analysis of news using Theo van Leeuwen's approach reveals the use of various strategies in shaping narratives. The news implements inclusion and exclusion, utilizing passivization, nominalization, and objectification-abstraction to guide the reader's understanding. This approach also involves nomination-categorization and nomination-identification, establishing the identities of actors, victims, and families. Keywords: Gender Discrimination, News, Critical Discourse Analysis, Theo Van Leeuwen